Penerapan Packaging dan Sales Promotion Pada Usaha Aksesoris Chattin Bers di Gudang Arang Ambon - Dian Sutiksno; Wulan Ningsih Reasoa; Victor Nahuway; Fentje Salhuteru (Fakultas Ekonomi Universitas Islam 45, 2022)
The problem of MSMEs in Indonesia generally lies in capital and product marketing, so that many government programs have been implemented to improve the capabilities of MSMEs in management and technical aspects. For this reason, promotion and attractive packaging are needed to introduce accessory products that can be enjoyed by consumers in that place. In this study, the application of packaging and Sales Promotion is made that can help Chattin Bers accessories entrepreneurs to promote accessories using brochures and can sell them online through social media (Facebook, Instagram, and Shopee). The social media account used is a business account so that it can make it easier for the community so that it can make it easier for people to find and buy Chattin Bers accessories.